2008
DOI: 10.1080/13607860802154408
|View full text |Cite
|
Sign up to set email alerts
|

The role of psychological variables in explaining depression in older people with chronic pain

Abstract: The present study confirms the important role of cognitive-behavioural variables in the discrimination between older adults who suffer pain with and without symptoms of depression. Moreover, certain variables that in young adults had been seen to play a non-adaptive role, such as ignoring pain sensations, were seen to have an adaptive function in the elderly. Also, our results are in support of depression models - such as Abramson's Hopelessness Model - proposing that depression in chronic pain patients, unlik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 59 publications
3
20
0
Order By: Relevance
“…Besides this, differences in specifications of the study sample, such as chronic disease versus injuries and limited variance of the self-efficacy scale (M = 3.22, SD = 0.51), might partly explain the missing associations. Only Lopez-Lopez et al [57] reported similar findings in older patients with chronic arthritis. Depressed patients did not differ in self-efficacy from non-depressed patients.…”
Section: Discussionsupporting
confidence: 50%
“…Besides this, differences in specifications of the study sample, such as chronic disease versus injuries and limited variance of the self-efficacy scale (M = 3.22, SD = 0.51), might partly explain the missing associations. Only Lopez-Lopez et al [57] reported similar findings in older patients with chronic arthritis. Depressed patients did not differ in self-efficacy from non-depressed patients.…”
Section: Discussionsupporting
confidence: 50%
“…Research on attribution theory in patient populations has shown that different attribution targets for cause of disease (e.g., self-blame, otherblame, God-blame) can affect health variables (e.g., Lopez-Lopez, Montorio, Izal, & Velasco, 2008;Pargament & Hahn, 1986;Voth & Sirois, 2009). Forgiveness of others occurs because an individual has been wronged, and involves hostility, anger, and vengefulness.…”
Section: Particularly Relevant Dimensions Of Forgivenessmentioning
confidence: 99%
“…The mixture modeling technique maps longitudinal response patterns based primarily on the intrinsic properties of the data structure (Muthén, 2004), which largely overcomes the limitation of priori assumptions in group assignment. It has been suggested that the middle-aged population is at particularly high risk of psychological dysfunction following pain, and that psychosocial mediators of pain-depression association might be age specific (López-López et al, 2008). Hence the ages of the sample were limited to 45 to 65 years old, in order to minimize the impact of age on the trajectories.…”
Section: Introductionmentioning
confidence: 99%